Analisis Identitas dan Integrasi Nasional Bangsa Indonesia - Wijaya, Alit Rio; Syahirah, Cut Nur Indah; Agnesia, Fiona (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The identity and national integration of the Indonesian people are very important things to maintain. Identity is a sign of identification of the nation itself, while integration is a form of unity aimed at the Indonesian nation today. In this research, the aim is to find out how the identity and integration of the Indonesian nation is implemented and the importance of these two discussions. The research method used in this research is a qualitative method using a library approach. From this research, the results are that identity and integration are things that cannot be separated and are very important in maintaining the integrity of the Indonesian nation..